DOI: 10.17077/etd.bvuj47ji
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of transition-metal polyphosphides

Abstract: This dissertation describes the synthesis of several transition-metal polyphosphides including orthorhombic FeP 2 , cubic CoP 3 , cubic NiP 2 , monoclinic PdP 2 and monoclinic CuP 2. The investigation of these materials was initiated by the discovery of MP x formation upon reacting a metal halide with molecular yellow P 4 in superheated toluene. When these MP x products were annealed at moderate temperatures (350-500 °C), crystalline phosphorus-rich phases were produced. We found that these phases have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 101 publications
(169 reference statements)
0
1
0
Order By: Relevance
“…Although CuP 2 is the more thermodynamically stable phase [17], common wet-chemical synthesis (with phosphine) always generates Cu 3 P [20]. CuP 2 can be synthesized by ball-milling [21,22], solvothermal [23], and solid-gas reaction [24], which usually requires high temperature or vacuum annealing. Barry et al reported that the synthesis of amorphous CuP 2 by mixing copper chloride and white and red phosphorus as a solid pallet can lower the annealing temperature to 500 • C [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although CuP 2 is the more thermodynamically stable phase [17], common wet-chemical synthesis (with phosphine) always generates Cu 3 P [20]. CuP 2 can be synthesized by ball-milling [21,22], solvothermal [23], and solid-gas reaction [24], which usually requires high temperature or vacuum annealing. Barry et al reported that the synthesis of amorphous CuP 2 by mixing copper chloride and white and red phosphorus as a solid pallet can lower the annealing temperature to 500 • C [25].…”
Section: Introductionmentioning
confidence: 99%